2016
DOI: 10.1139/cjas-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

Can potential for dark cutting be predicted by phenotype? Relationship between sex, carcass characteristics, and the incidence of dark cutting beef

Abstract: Recent research indicated that reduced carcass muscling and weight are associated with beef dark cutting. Existing data from a single farm (44 heifers, 136 steers) from three normal beef quality grades (Canada AAA, AA, A) and the dark cutting grade (Canada B4) (n = 35, 106, 28, and 11, respectively) were used to identify relationships between sex, live animal, and carcass characteristics and the incidence of dark cutting. Categorical modelling showed a trend (P = 0.106) for heifer carcasses to have a greater p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
1
2
0
1
Order By: Relevance
“…Based on the pH threshold of 5.7 and AUS‐MEAT color reference standards (a 1 to 7 scale), McGilchrist and others () found that DC carcasses had reduced eye muscle area, carcass weight, and subcutaneous rib fat depth. The results of this research were supported by those of Holdstock and others () and Mahmood and others (b), which showed that DC carcasses as assessed by subjective color measures, both with atypical (ultimate pH 5.8 to 6.0) and typical (pH greater than 6.0) ultimate pH values, had decreased carcass and muscle weights relative to normal carcasses. That physiological attributes may be indicators of the likelihood of DC suggests that cattle that produce a DC carcass may not be experiencing additional stress prior to slaughter through transport and handling, but that some cattle have less resistance to or recover more slowly from physical stress than others (McGilchrist and others ; Holdstock and others ; Mahmood and others ).…”
Section: Contributing Factors To DCsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the pH threshold of 5.7 and AUS‐MEAT color reference standards (a 1 to 7 scale), McGilchrist and others () found that DC carcasses had reduced eye muscle area, carcass weight, and subcutaneous rib fat depth. The results of this research were supported by those of Holdstock and others () and Mahmood and others (b), which showed that DC carcasses as assessed by subjective color measures, both with atypical (ultimate pH 5.8 to 6.0) and typical (pH greater than 6.0) ultimate pH values, had decreased carcass and muscle weights relative to normal carcasses. That physiological attributes may be indicators of the likelihood of DC suggests that cattle that produce a DC carcass may not be experiencing additional stress prior to slaughter through transport and handling, but that some cattle have less resistance to or recover more slowly from physical stress than others (McGilchrist and others ; Holdstock and others ; Mahmood and others ).…”
Section: Contributing Factors To DCsupporting
confidence: 83%
“…That physiological attributes may be indicators of the likelihood of DC suggests that cattle that produce a DC carcass may not be experiencing additional stress prior to slaughter through transport and handling, but that some cattle have less resistance to or recover more slowly from physical stress than others (McGilchrist and others ; Holdstock and others ; Mahmood and others ). Specifically, research into the incidence of DC in heifers and steers in Canada (Mahmood and others ,b) substantiated that heifers most likely to cut dark had reduced weaning and slaughter weights, and that cattle regardless of gender most likely to cut dark had decreased carcass weights and longissimus thoracis muscle areas at the 12th to 13th rib interface.…”
Section: Contributing Factors To DCmentioning
confidence: 99%
“…Pearson's correlation coefficient analysis was performed to determine linear relationships between independent variables including RFI and RFIf values using R with the package Hmisc version 4.0-2, and a Bonferroni correction was used to compensate for the likelihood of type I error. Twenty-nine comparisons were made; thus, correlations were considered significant at P = 0.0017 as calculated by 0.05/29 (Mahmood et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…El estrés crónico y la exposición de largos plazos de estrés agudo, justo antes de ser sacrificado, hacen que las reservas de glucógeno muscular se consuman rápidamente (2) , reduciendo la cantidad de ácido láctico que se forma por la glucólisis anaerobia en el músculo luego de la muerte del animal, lo cual provoca la presencia de carne DFD, también llamada Corte Oscuro (16,17) . Existen diferentes factores intrínsecos que aumentan el riesgo de una mayor presencia de carne DFD tales como: el origen racial (más frecuente en Bos indicus) (18,19) , el sexo (mayor en machos enteros) (7,20) , el peso (menos común en ganado de mayor peso vivo) (21,22) , la cantidad de grasa (se presenta más frecuentemente con valores bajos en el espesor de la grasa subcutánea) (4,23) y la edad (es más frecuente en animales viejos) (24,25) . Las condiciones ambientales también influyen en la presencia de carne DFD, las temperaturas extremas provocan estrés por calor o por frío (26,27) .…”
Section: Introductionunclassified